The Royal Version of Dalang during the Reign of King Rama III: The Art of Playwriting for a Court Dance-Drama - Jatuthasri, Theneerat (Journal of Arts and Thai Studies, 2024)
Objectives: This research article aims to examine the art of playwriting in the royal version of Dalang written during the reign of King Rama III and compare it with earlier versions of the Dalang play. Methods: This documentary research involves analyzing the elements of the royal version of Dalang written during the reign of King Rama III and comparing the text with other versions of the Dalang play, including that of King Rama I and the Ayutthaya versions, in order to better understand the art of playwriting in the royal version of Dalang written from the reign of King Rama III. Results: The royal version of Dalang written during the reign of King Rama III is court dance-drama. The poet employs various techniques composing the play to ensure the play is suitable for performance, including: 1) integrating the plot, content, and descriptions from earlier versions of Dalang, including King Rama I’s Dalang and the Ayutthaya versions of Dalang, into the play; 2) inserting certain descriptions that could be transformed into outstanding beautiful dances in-line with the court dance-drama tradition; 3) modifying the narration for concise continuity of the story; and 4) using artistic language. Application of this study: The results of the study may contribute to both literary studies and the field of performing arts. The study’s results may offer guidance for other studies of Thai dance-dramas and serve as an example for creating a court dance-drama. Additionally, this study may play a role in sparking the interest of Thai artists to adapt the play for performance.